PENERAPAN REGRESI GENERALIZED POISSON UNTUK MENGATASI FENOMENA OVERDISPERSI PADA KASUS REGRESI POISSON - EKA PUTRA, I PUTU YUDANTA; NILA KENCANA, I PUTU EKA; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2013)
The Poisson regression is generally used to analyze the response variable that is a discrete data. Poisson regression has assumption which must be met, that is condition equidispersion. But in fact this assumption is often violated, that is the value of the variance is greater or less than the mean value. The condition when value of the variance is greater than the mean value is called overdispersion. One method that can be used for overdispersion data is Generalized Poisson regression. In this research, it was found that the Generalized Poisson regression method was better than Poisson regression method.
Keywords: Poisson Regression; Overdispersion; Generalized Poisson regression